International Publications on Radicalism and Terrorism in Indonesia: A Bibliometric Assessment - Munawar Fuad (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2020)
This article analyses international publications on radicalism and terrorism in Indonesia in the Scopus database. This study employs a bibliometrics study to designate a set of quantitative methods of analysis of international scientific publications on radicalism and terrorism in Indonesia. Data was collected from search results in the Scopus database with a combination keyword "radicalism OR terrorism OR Fundamentalism IN Indonesia" in three categories: article titles, article abstracts, and article keywords in publication period, 2001-2019. The results found 414 scientific publications relating to radicalism and terrorism. The highest number was in 2019, with 49 scientific publications (11.8%). The highest amount was obtained from publishing in Jane’s Defense Weekly, a publisher in the United Kingdom (UK) that provides open-source for global intelligence agents with 12 publications (2.8%). The most prolific writer is Julie Chernov Hwang, with seven articles. He is an associate professor in politics and international relations department at Goucher College, Baltimore, Maryland (MD), United States. However, of the total scholars who conducted international publications in radicalism and terrorism study, the first rank was occupied by Indonesian scholars with 128 papers (30.9%). It shows that Indonesian scholars are serious about conducting radicalism and terrorism studies in their country. Whereas, publications forms that most contributed to radicalism and terrorism study were international journal articles with 273 publications (65.9%). The radicalism and terrorism study is the most studied in social sciences studies with 270 publications (65.2%).